(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
This is a perspective study of 70 cadavers to identity hemorrhages by shaming iron an uncial. The amount of them normal tissue is 20 μg/g in skin and 40 μg in muscle. In bleeding carry it is 35 μg/g in skin and 53 gm/g in muscle the amount of iron in the injured pant in 3.5 times hyaline than in normal tissue.